The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1134/s0006297906030047
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity of IgG antibodies from blood of acquired immunodeficiency syndrome patients

Abstract: Proteolytic activity of polyclonal IgG antibodies (Abs) from the blood of AIDS patients was analyzed for the first time. These Abs were shown to display higher activity in hydrolysis of beta-casein than in hydrolysis of human immunodeficiency virus (HIV)-1 reverse transcriptase (RT) or human serum albumin (HSA). Several abzymatic criteria were applied and it was shown that RT, HSA, and beta-casein hydrolyzing activities are an intrinsic property of polyclonal Abs from AIDS patients. Casein-hydrolyzing Abs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 42 publications
5
69
0
Order By: Relevance
“…It was recently shown that pIgGs and/or pIgMs of HIV‐infected patients catalyze hydrolysis of DNA, HIV‐1 reverse transcriptase, and integrase . Human casein and serum albumin were the first examples of protease Abs against human proteins appearing in humans after viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that pIgGs and/or pIgMs of HIV‐infected patients catalyze hydrolysis of DNA, HIV‐1 reverse transcriptase, and integrase . Human casein and serum albumin were the first examples of protease Abs against human proteins appearing in humans after viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1995, Ravetch et al and other groups 50,54,55 have published a series of papers indicating that glycosylation of IgGs in rheumatoid arthritis (RA) is one of the crucial underlying molecular mechanisms causing inflammation. IgG antibodies are potent inducers of proinflammatory responses.…”
Section: Figure 11mentioning
confidence: 99%
“…Other hypotheses implicate viral DNA, 7,18,47,50 microbial DNA, and/or unmethylated CpG motifs within the DNA of any species 56 all of which may be interesting to the innate immune system. Could a new mechanism of antigen recognition be taking place, omitting the classical antigen-presentation loop to the T-cells and their helper response?…”
Section: Figure 11mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated with HIV patients that in case of viral infections with subsequent development of autoimmune reactions, generation of Abs against viral proteins that also have catalytic activity occurs. These abzymes hydrolyze specifically only reverse transcriptase [214] and HIV integrase [215 217].…”
Section: Natural Abzyme Nucleasesmentioning
confidence: 99%